Psychological distance asymmetry: The spatial dimension vs. other dimensions - Zhang, Meng; Wang, Jing (Journal of Consumer Psychology, 2009)
AbstractIn this research we demonstrate an asymmetry between the spatial dimension and the other three dimensions of psychological distance—i.e., the temporal, social, and hypothetical dimensions. The first study shows that a distal prime along the spatial dimension leads to greater perceived distance along the other three dimensions, but not the other way around. We theorize that this is because people understand temporal, social, and hypothetical distance in terms of spatial distance. Hence, symmetric priming effects should occur when similarities between the spatial dimension and other dimensions are highlighted. Indeed, the last three studies, using multiple operationalizations, show that such priming effects could become symmetric when people engage in relational processing.